Pengesahan proyek program bantuan pembangunan daerah tingkat II tahun 1985/1986 di Propinsi Dati-I Sumatera Utara (Gubernur Kepala Daerah Tingkat I Sumatera Utara, 1985)
Collection of formal approvals of the Governor for the implementation of 1985/86 development projects at the Kabupaten level in North Sumatra.